Nucleic acid sensing and immunity. - Vanpouille-Box, Claire; Galluzzi, Lorenzo (International review of cell and molecular biology ;, 2019)
'Nucleic Acid Sensing and Immunity - PART A, ' Volume 344, provides a comprehensive overview of the nucleic acid machinery, from plants to mammalians, as well as their regulation. Specific chapters in this updated release include Molecular bases of discrimination between self from non-self nucleic acids, Intracellular RNA sensing in mammalian cells, Nuclear DNA damage and nucleic acid sensing, Negative regulation of nucleic acid sensing, Dendritic cell responses to exogenous nucleic acids, Activating the nucleic acid-sensing machinery for anticancer immunity, and Nucleic acid sensing and inflammasomes, amongst other topics. Key Features: Provides an accurate, state-of-the-art resource on RNA sensing; Includes the work of a well-known tumor immunologist; Links intestinal host defense and viral nucleic acid sensing; Presents a chapter on the negative regulation of DNA sensing, a timely topic. Readership: Immunologists to tumor immunologists and DNA damage biologists. --